The impact of RCA and fly ash on the mechanical and durability properties of polypropylene fibre-reinforced concrete exposed to freeze-thaw cycles and MgSO4 with ANN modeling - Yavuz Bayraktar, Oguzhan; Salem Taher Eshtewı, Samı; Benli, Ahmet; Kaplan, Gokhan; Toklu, Kenan; Gunek, Furkan (Elsevier BV, 2021)
Abstract An experimental study has been conducted to investigate the impact of recycled coarse aggregate (RCA) and fly ash (FA) on the transport, mechanical and durability properties of polypropylene fiber reinforced concretes. In this context, nine concrete mixtures with 25% FA as cement replacement (by wt.) and nine mixtures without FA were produced. RCA was used to replace natural coarse aggregates (NCA) at 0, 25 and 50% by wt. in all concrete mixtures. In addition, polypropylene fiber (PPF) was added to concrete mixtures at 0, 3 and 6% by volume. Mechanical performance was evaluated by compressive, splitting tensile strength at 7, 28 and 90 days and Schmidt rebound hammer at 90 days. Dry bulk density, water absorption, apparent porosity and sorptivity of concrete were also evaluated. Durability performance of concretes was evaluated by exposing to 50,100 and 150 freeze-thaw cycles and MgSO4 attack. Abrasion test on the concretes was also performed. After performing durability tests, compressive, splitting tensile strength, ultrasonic pulse velocity, microstructural observations and mass loss of the concretes were assessed. An artificial neural network (ANN) was also modeled for predicting experimental data. The results indicated that combined use of RCA, FA and PPF improved the compressive strength considerably and approximately 60 MPa was obtained in concretes with 25 and 50% RCA. The use of RCA in concretes with 25% FA has improved the mechanical properties. The mixture with 25% RCA, 6%PPF and without FA and the mixture with 50% RCA, 3%PPF and FA showed the best abrasion resistance. Reference and the mixture with 0% RCA, 25% FA and 6% PPF exhibited the lowest strength loss after the MgSO4 attack. Reference and the mixture with 25% RCA, 25% FA and 3% PPF performed the best after 100F-T cycles in terms of compressive strength. With the Bayesian regularized algorithm, material quantities for the target concrete properties can be obtained. The main outcome of this study is that using RCA, FA and PPF in concrete can give better performance in terms of mechanical and durability performance than normal concrete.
Keywords: 12. Responsible consumption